LENGTH-WEIGHT RELATIONSHIP IN PENNAHIA MACROPTHALMUS (BLEBKER) AND JOHNIUS CARUTTA (BLOCH) - Rao, T Appa (Indian Journal of Fisheries, 2011)
No significant difference was noticed between the length-weight relationahips in males and females in both Pennahia macropthalmus and Johnius carutta. Hence a common equation for both sexeS in each species has been given.